Influence of Models Guided Doscovery Learning on Class VIII Students' Mathematical Creative Thinking Ability of Mts Ma'arif Nu 04 Tamansari - Amany, Septy Faiqotul; Miatullabibah (International Journal of Research in Mathematics Education, 2023)
The background of this research is the low ability to think creatively mathematically in class VIII students at MTs Ma'arif NU 04 Tamansari, because the teacher's learning uses the lecture method, where students only pay attention to explanations, so students are less interested in learning and have difficulty understanding the material. Therefore, researchers use learning models that can improve students' creative thinking abilities, one of which is the Guided Discovery Learning learning model. The Guided Discovery Learning Learning Model is a learning model that prioritizes student activity in processing information or learning materials through guidance from the teacher and collaboration between students. The research design used in the study was the Pretest and Posttest Control Group. In this study, the population taken was students of class VIII MTs Ma'arif NU 04 Tamansari, namely class VIII A, VIII B, VIII C, VIII D, and VIII E. While the sample was class VIII B and VIII C. Sampling in this study using the technique of Convanience Sampling (Desirability Sampling). The data collection technique used in this study was in the form of essay tests in the form of pretest and posttest. Data analysis techniques using the t test. The results of this study are that the Guided Discovery Learning learning model is carried out very well and the Guided Discovery Learning learning model influences the ability to think creatively mathematically in class VIII students.